Propuesta para la creación del departamento de seguridad industrial y salud ocupacional de la Empresa RELEV S.A. del cantón Santo Domingo año 2014 - Bajaña Medina, Reinalddo Pertini (2015)
This research has the general objective of developing a proposal for the creation of the Department of Industrial Safety and Occupational Health RELEV COMPANY SA For the realization of the risk matrix the results of the surveys were considered and determined: the risks in the company, the level of impairment, the exposure level, the probability level, the level of consequence this to determine the level of risk to which workers are exposed, this served to make the risk map of the company determines that the places of greatest risk as palm, pastures, livestock, mechanics, where the company will improve labor safety and hygiene he also managed to establish procedures manuals for the use of personal protective equipment, agricultural machinery and tools in the company, the same that determine the next steps for the correct use within the activities in the various business tasks besides define responsible and which document to register the same, the organization of this department which defines the number of people who will work in it and the different activities that must meet each based on the current regulations established in Ecuador , culminating investment company must do to establish this department with the value amounting to $ 19,170.76, necessary equipment, furniture, local arrangements, medicines etc. are budgeted, and compared with the costs that the company would conduct for the payment of compensation to workers by not having this department responsible for conducting the management of occupational health and safety.